NCOG-28. THE IMPACT OF MULTIPLE MENINGIOMAS ON PROGRESSION-FREE SURVIVAL: A 10-YEAR MULTI-CENTER STUDY. (12th November 2021) - Ramos-Fresnedo, Andres; Domingo, Ricardo; Sanchez-Garavito, Jesus; Perez-Vega, Carlos; Akinduro, Oluwaseun; Jentoft, Mark; Brown, Paul; Porter, Alyx; Bendok, Bernard; Link, Michael; Middlebrooks, Erik; Trifiletti, Daniel; et al.
Abstract: INTRODUCTION: Multiple meningiomas (MM) occurs in up to 18% of meningioma patients and progression data are scarce. The objective of this study is to explore the influence of number of lesions and clinical characteristics on progression-free survival (PFS) and time to a second intervention (TTSI) in patients with WHO grade 1 meningiomas. METHODS: We retrospectively reviewed records of all adults diagnosed with a meningioma at our three main sites from January 2009 to May 2020. Progression was considered as time from diagnosis until radiographic progression of the originally resected meningioma. A secondary analysis was carried to evaluate the time from diagnosis to time of a second intervention. Univariable and multivariable analyses were conducted to assess whether number of lesions or any associated variables (age, sex, race, radiation, location, and extent of resection) had a significant impact on PFS and TTSI. RESULTS: 838 patients were included. Log-rank test evaluating PFS and TTSI between single and multiple lesions showed significantly shorter progression for MM (p< 0.001 and p< 0.001, respectively). Multivariable Cox regression showed significantly inferior PFS on MM vs. single lesion (HR 2.262 [CI 95%, 1.392-3.677], p=0.001) and a significantly inferior TTSI for patients with MM vs. single meningioma (HR 2.377 [CI 95%, 1.617 – 3.494], p=0.001). When input as a continuous variable, PFS was significantly inferior for each additional meningioma (HR 1.350 [CI 95% 1.074-1.698], p=0.010) and TTSI is significantly inferior as well (HR 1.428 [CI 95% 1.189 – 1.716], p< 0.001). African-Americans had an inferior PFS when compared to Non-Hispanic White patients (HR 3.472 [CI 95% 1.083-11.129], p=0.036). CONCLUSION: The PFS of meningiomas is influenced by the number of lesions present. Patients with MM are more prone to undergo a second intervention for progressive disease. Hence, a closer follow-up may be warranted in patients who present with multiple lesions.